Batasan Yuridis Pengecualian Pidana Pengkajian Paham Komunisme/Marxisme-Leninisme Untuk Kepentingan Ilmu Pengetahuan Dalam KUHP Baru - Ahmad Fadli Fathurrohman; Nur Rohim Yunus (UIN Syarif Hidayatullah Jakarta, 2026)
The amendment to the Criminal Code is a significant phenomenon in the dynamics of criminal law in Indonesia. The amendment to the law has led to updates and even created new articles for various criminal acts in Indonesia. One of the new articles that emerged in the amendment is the emergence of an article prohibiting the spread of Communism/Marxism-Leninism in Indonesia in articles 188-189, but on the other hand, Article 188 paragraph 6 contains an exception (Criminal Exception) to study these ideologies for scientific purposes. From this, this study aims to discuss the legal limitations of the study of these ideologies in the scientific sphere so that they are not misused by related parties. This study concludes that the limitation on the permissibility of studying Communism/Marxism-Leninism for scientific purposes is as long as the activity does not include the dissemination or propaganda of these ideologies.